2004
DOI: 10.1243/0954409041319597
|View full text |Cite
|
Sign up to set email alerts
|

An approach to evaluate the service life of rubber springs used in rail vehicle suspensions

Abstract: The stress-endurance (S-N) method has been widely used in metal fatigue in the railway industry over many years. However, when this method is applied to rubber-like materials, it seems not as successful as when it is applied to metallic materials. Recently, an integrated fatigue evaluation programme has been carried out with the aim of improving the design of antivibration components in response to the increasing demands of the rail operating environment. This programme will also make simulations more reliable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 3 publications
0
34
0
Order By: Relevance
“…By using the S-N curve obtained from uniaxial loading, they performed fatigue life predictions and proposed a threedimensional effective stress criterion describing an ellipsoidal failure envelope for fatigue failure based on principal stress values. They conducted fatigue tests on two types of rubber springs in the longitudinal direction under uniaxial loading and their experimental results indicated good agreement with the predictions for both crack initiation location and direction [9].…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…By using the S-N curve obtained from uniaxial loading, they performed fatigue life predictions and proposed a threedimensional effective stress criterion describing an ellipsoidal failure envelope for fatigue failure based on principal stress values. They conducted fatigue tests on two types of rubber springs in the longitudinal direction under uniaxial loading and their experimental results indicated good agreement with the predictions for both crack initiation location and direction [9].…”
Section: Introductionmentioning
confidence: 76%
“…Their study showed the capability of nonlinear quasi-static FE simulation for modeling geometric and material nonlinearities of elastomeric components in product design and failure analysis. They analyzed fatigue life of anti-vibration rubber springs used in a rail vehicle suspension system [7][8][9]. Mooney-Rivlin hyper-elastic material model and FEA were used in their study to obtain the stress contour.…”
Section: Introductionmentioning
confidence: 99%
“…Equation (1) has been widely used to predict material response under the loading portion of a loading-unloading process. However, it is not suitable for prediction of the response during the unloading portion or the reloadingunloading process.…”
Section: Hyperelastic Models Of Rubber Materials Without Stress Softeningmentioning
confidence: 99%
“…Zerrin-ghalami and Fatemi 9 used a hyperelastic material model to predict the fatigue life of an automobile cradle mount. Luo et al 3 , Luo et al 10 and Lu and Wu 11 have developed a threedimensional effective stress criterion that considers all the principal stress tensors, and used it to predict fatigue crack initiation; they validated their results against several engineering applications of anti-vibration rubber components. Also Luo et al 12,13 and Luo et al 14 performed investigations on rubber springs in order to solve customer-raised issues.…”
Section: Introductionmentioning
confidence: 99%